What Makes an Individual Inclusive of Others? Development and Validation of the Individual Inclusiveness Inventory - Cecily Josten; Grace Lordan (Institute of Labor Economics (IZA), 2024)
This study develops and validates the 'Individual Inclusiveness Inventory'. Collaboration and inclusion are key contributors to successful work outcomes in an increasingly diverse workforce. We capture what makes an individual inclusive of others at work. We define an inclusive individual as someone who actively includes individuals in a group and encourages diversity of thought and background but still encourages the group in a way as to maximise performance and productivity. To develop the 'Individual Inclusiveness Inventory' we combine a deductive and inductive approach: we generate scale items based on the existing literature on inclusion and interviews with 14 experts in diversity and inclusion. The items are then reduced using exploratory factor analysis and confirmed using confirmatory factor analysis in two samples of working professionals in the UK. This results in a two-factor solution where factor 1 'Belonging and Uniqueness' captures the importance of fostering belonging and uniqueness at work and factor 2 'Challenge and Openness' captures being open to challenge and being challenged. We test the predictive validity of the two-factor solution with respect to work outcomes. We find that 'Challenge and Openness' is positively related to all work outcomes studied including income. This link to productivity is intuitive for individuals who are open to challenge are also likely competitive and innovative. 'Belonging and Uniqueness' is positively related to the number of people managed and perceived comparative seniority and happiness. This factor is less predictive of productivity as fostering belonging and uniqueness is likely more about group outcomes or happiness.
Keywords: J4; 330; inclusion; collaboration; measurement; belonging; challenge; openness